The mediating role of depression on the association between physical activity and cognitive function among older adults - Zhang, HuanRui; Tian, Wen; Qi, GuoXian; Wei, XiuFang (Frontiers in Aging Neuroscience, 2025)
BackgroundPrevious studies had showed that physical activity (PA) can effectively reduce cognitive decline. Nonetheless, it is still unclear whether depression can mediate the relationship between PA and cognitive decline.MethodsThis study encompassed 2,681 older adults (≥ 60 years) from the National Health and Nutrition Examination Survey (NHANES) study during 2011–2012 and 2013–2014 cycles. PA was assessed, including recreation activity, work activity, and walking/bicycling. Depression was evaluated using the Patient Health Questionnaire-9, and cognitive function was assessed through a series of cognitive tests at the Mobile Examination Center. Utilizing weighted multivariable linear regression, we assessed the associations among PA, depression, and cognitive function. Additionally, a mediation model was employed to investigate how depression mediates the relationship between PA and cognitive decline.ResultsWe found that only moderate to high-intensity recreation activity and depression were associated with better cognitive function, including performance on the Animal Fluency Test (AFT), the Digit Symbol Substitution Test (DSST), and the overall cognitive function (composite z-score), following adjustments for potential confounding factors. Depression emerged as a mediator in the relationship of moderate to high-intensity recreation activity with AFT, DSST, and the composite z-score, mediating 6.5%, 12.3%, and 10.5% of the overall association, respectively. Furthermore, in the sensitivity analysis that excluded participants with a history of stroke, the sensitivity analysis results remained consistent and stable.ConclusionThis study found that in older adults, increasing engagement in moderate to high-intensity recreation activity, rather than work activity or walking/bicycling, is related with a reduction in cognitive decline. Notably, depression emerged as a pivotal mediating factor in this relationship.